Impact of Unregulated Privatization of Education in Nigeria: An Appraisal of the Lead City University- National Universities Commission Dispute - Kalama, John; Etebu, Charity E.; Martha, Charles A.; John, Sophia M. (Richtmann Publishing, 2011)
The proliferation of private institutions (Nursery, primary, secondary schools and tertiary institutions) throughout thecountry coupled with frequent closure of schools prompted this research. The findings in this study show that the privatization ofeducation that took place between 1980 and 1990 through the granting of private licenses to individuals was doneindiscriminately without proper supervision and monitoring. Further investigations show that the beneficiaries of the privatizationexercise are either serving or retired senior public office holders. Thus, making it difficult to ensure compliance (standards). Thestudy also reveal that while monitoring, regulation and control of tertiary institutions in the country is effective through theNational Universities Commission (NUC), regulation and control is completely absent at the nursery, primary, and secondaryschool levels. However, the systems political theory was applied while explaining and analyzing the subject-matter. In terms ofmethodology and scope, descriptive analysis and secondary sources of data (textbooks, published articles and journals) wererelied upon. Nevertheless, cases of unrest and other forms of crisis facing the education sector in Nigeria can be minimized andcurtailed if the government (local, state and federal) through its regulatory agencies (ministries, departments, boards andcommissions) conducts regular and periodic evaluation and supervision of existing private schools and institutions throughoutthe country. This will no doubt ensure compliance, prosecution and revocation of existing licenses of schools and institutions thatfail to meet approved standards.